Dampak Literasi Keuangan, Teknologi Finansial, dan Perilaku Keuangan terhadap Keputusan Investasi pada Mahasiswa Universitas PGRI Semarang Angkatan 2021 - Tri Bayu Atmaja; Rita Meiriyanti; Prianka Ratri Nastiti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the influence of financial literacy, financial technology, and financial behavior on investment decisions among students at the Universitas Persatuan Guru Republik Indonesia Semarang. The data used in this study is primary data, obtained through the distribution of questionnaires via Google Forms to students at the Universitas Persatuan Guru Republik Indonesia Semarang. The population of this study consists of students from the university, and the sampling technique used is probability sampling with purposive sampling. The sample was determined using the Slovin formula with a margin of error of 10%. The analysis tool used in this study is SPSS 26 to process and analyze the data. This study tests three hypotheses: H1, which states that financial literacy does not significantly affect investment decisions, H2, which states that financial technology does not significantly affect investment decisions, and H3, which states that financial behavior significantly affects investment decisions. The results of the study indicate that H1 is accepted, meaning that financial literacy does not significantly influence investment decisions. On H2, the results also show that financial technology does not significantly affect investment decisions. However, for H3, the results show that financial behavior significantly influences investment decisions. Therefore, it can be concluded that while financial literacy and financial technology do not have a significant impact on students' investment decisions, financial behavior plays a more dominant role in influencing their investment decisions. This study provides valuable insights for universities and other educational institutions to focus more on improving students' financial behavior as a strategic step in enhancing the quality of investment decisions